SPECIAL FEATURES OF CARCINOGENESIS OF COLON ADENOCARCINOMA - G. A. Raskin; S. V. Petrov; R. V. Orlova (Сибирский онкологический журнал, 2016)
Colorectal cancer is one of the most common malignancies and the leading cause of cancer-related death. There are 4 basic colon carcinogenic steps: malignant transformation of adenoma into carcinoma; HNPCC (hereditary nonpolyposis colon cancer); cancer «de novo»; chronic colitis malignant transformation. All of them, except for Lynch syndrome, are increasingly focused on stem tissue-committed cells as mutation targets and the source of malignancies. Subsequently, cancer stem cells are considered as the cause of chemoresistance of tumors, metastases and relapses. Thus, the study of the cell population can dramatically change approaches to the treatment of patients with colorectal adenocarcinoma.